Presentation of life-threatening invasive nontyphoidal Salmonella disease in Malawian children: A prospective observational study. - Calman A MacLennan; Chisomo L Msefula; Esther N Gondwe; James J Gilchrist; Paul Pensulo; Wilson L Mandala; Grace Mwimaniwa; Meraby Banda; Julia Kenny; Lorna K Wilson; Amos Phiri; Jenny M MacLennan; et al. (Public Library of Science (PLoS), 2017)
Nontyphoidal Salmonellae commonly cause invasive disease in African children that is often fatal. The clinical diagnosis of these infections is hampered by the absence of a clear clinical syndrome. Drug resistance means that empirical antibiotic therapy is often ineffective and currently no vaccine is available. The study objective was to identify risk factors for mortality among children presenting to hospital with invasive Salmonella disease in Africa. We conducted a prospective study enrolling consecutive children with microbiologically-confirmed invasive Salmonella disease admitted to Queen Elizabeth Central Hospital, Blantyre, in 2006. Data on clinical presentation, co-morbidities and outcome were used to identify children at risk of inpatient mortality through logistic-regression modeling. Over one calendar year, 263 consecutive children presented with invasive Salmonella disease. Median age was 16 months (range 0-15 years) and 52/256 children (20%; 95%CI 15-25%) died. Nontyphoidal serovars caused 248/263 (94%) of cases. 211/259 (81%) of isolates were multi-drug resistant. 251/263 children presented with bacteremia, 6 with meningitis and 6 with both. Respiratory symptoms were present in 184/240 (77%; 95%CI 71-82%), 123/240 (51%; 95%CI 45-58%) had gastrointestinal symptoms and 101/240 (42%; 95%CI 36-49%) had an overlapping clinical syndrome. Presentation at <7 months (OR 10.0; 95%CI 2.8-35.1), dyspnea (OR 4.2; 95%CI 1.5-12.0) and HIV infection (OR 3.3; 95%CI 1.1-10.2) were independent risk factors for inpatient mortality. Invasive Salmonella disease in Malawi is characterized by high mortality and prevalence of multi-drug resistant isolates, along with non-specific presentation. Young infants, children with dyspnea and HIV-infected children bear a disproportionate burden of the Salmonella-associated mortality in Malawi. Strategies to improve prevention, diagnosis and management of invasive Salmonella disease should be targeted at these children.